Preparation and characterization of Poly(lactic acid)/ Poly(ɛ-caprolactone)/ Glycidyl Methacrylate blends and the effects of electron beam irradiation on the blends - Chee, Wei Kit (2013)
This research focused on blending of Poly(lactic acid) (PLA) with Poly(ε- caprolactone) (PCL) in order to overcome the brittle character of PLA matrix. Properties of PLA was successfully tuned to ductile however poor compatibility between these polymers limited the extend of improvement. Thus, Glycidyl Methacrylate (GMA) was utilized as interfacial compatibilizer to improve the interfacial compatibility of the non-miscible components. Besides, the effects of electron beam irradiation on mechanical properties of compatibilized blends were studied as well. The properties of PLA/PCL blends were improved significantly by addition of GMA by 3 wt%. FT-IR spectra indicated slight interaction between GMA and PLA matrix, in agreement with the improvement in mechanical properties. Elongation at break of the blend increased dramatically from 17.1% to 327% indicating better dispersion of PCL in PLA matrix as well as improvement interfacial adhesion. Decrease in flexural strength and modulus upon addition of GMA designated that the specimens were tuned from rigid to deformable. Besides, significant increase in impact strength from 418.36 J/m to 802.35 J/m was also recorded upon addition of GMA. Thermal properties of the blends were studied via Thermogravimetric Analysis (TGA) and Dynamic Mechanical Analysis (DMA). TGA revealed addition of 3 wt% GMA resulted slight improvement in thermal stability of the blend. In addition, DMA analysis showed that glass transition temperature (Tg ) of PLA in the blend shifted significantly to a lower temperature region with addition of GMA, indicating improved compatibility of the components. Scanning electron microscopy (SEM) was utilized to study the fracture surface morphology of the blends. The random and fibrous structure of PLA/PCL blend was tuned to a finer dispersion morphology upon addition of GMA.From water absorption analysis, it can be deduced that the addition of GMA influence the water uptake affinity of the blends to slightly higher level. However, the total increment in weight due to water absorption was considered minor (less than 1%). Soil burial degradation analysis revealed that the rate of degradation of PLA was relatively low. Besides, the addition of GMA did not significantly influenced the rate of degradation. Mechanical study on the irradiated specimens showed that the compatibilized blends were still remained ductility upon irradiation up to 10 kGy. Besides, slight increment was recorded on tensile strength when irradiation dosage varied from 10 to 15 kGy. Elongation at break dropped remarkably with increasing irradiation dosage up to 25 kGy, following by gradual decrement in tensile strength and modulus. However, blends added with GMA showed better resistivity upon irradiation, noted by high tensile strength and modulus values were retained upon irradiated at 25 kGy of dosage. FT-IR analysis revealed no shift in wavenumber occurred as a function of irradiation, indicating no interactions occurred. Water absorption analysis showed that irradiated specimens absorbed less water, however soil burial degradation test recorded no enhancement on the rate of degradation of the specimens upon irradiation.